2010 Gynecologic Cancer InterGroup (GCIG) Consensus Statement on Clinical Trials in Ovarian Cancer: Report From the Fourth Ovarian Cancer Consensus Conference. Issue 4 (1st April 2011) - Stuart, Gavin C.E.; Kitchener, Henry; Bacon, Monica; duBois, Andreas; Friedlander, Michael; Ledermann, Jonathan; Marth, Christian; Thigpen, Tate; Trimble, Edward
Abstract : 2010 Gynecologic Cancer InterGroup (GCIG) consensus statement on clinical trials in ovarian cancer. This report provides the outcomes from the Fourth Ovarian Cancer Consensus Conference.